(untitled) - Patterson, James; 1947-; Paetro, Maxine (Little, Brown and Company, 2015)
"With San Francisco under siege and everyone a suspect, the Women's Murder Club must risk their lives to save the city--and each other"--
Keywords: Women's Murder Club (Imaginary organization); Fiction; Policewomen; Fiction; California; San Francisco (Calif.); Fiction; Suspense fiction; Mystery fiction